Diagnostic algorithms in Charcot–Marie–Tooth neuropathies: experiences from a German genetic laboratory on the basis of 1206 index patients. Issue 1 (29th April 2015) - Rudnik‐Schöneborn, S.; Tölle, D.; Senderek, J.; Eggermann, K.; Elbracht, M.; Kornak, U.; von der Hagen, M.; Kirschner, J.; Leube, B.; Müller‐Felber, W.; Schara, U.; von Au, K.; et al.
Abstract : We present clinical features and genetic results of 1206 index patients and 124 affected relatives who were referred for genetic testing of Charcot–Marie–Tooth (CMT) neuropathy at the laboratory in Aachen between 2001 and 2012. Genetic detection rates were 56% in demyelinating CMT (71% of autosomal dominant (AD) CMT1/CMTX), and 17% in axonal CMT (24% of AD CMT2/CMTX). Three genetic defects ( PMP22 duplication/deletion, GJB1/Cx32 or MPZ/P0 mutation) were responsible for 89.3% of demyelinating CMT index patients in whom a genetic diagnosis was achieved, and the diagnostic yield of the three main genetic defects in axonal CMT ( GJB1/Cx32, MFN2, MPZ/P0 mutations) was 84.2%. De novo mutations were detected in 1.3% of PMP22 duplication, 25% of MPZ/P0, and none in GJB1/Cx32 . Motor nerve conduction velocity was uniformly <38 m/s in median or ulnar nerves in PMP22 duplication, >40 m/s in MFN2, and more variable in GJB1/Cx32, MPZ/P0 mutations. Patients with CMT2A showed a broad clinical severity regardless of the type or position of the MFN2 mutation. Out of 75 patients, 8 patients (11%) with PMP22 deletions were categorized as CMT1 or CMT2. Diagnostic algorithms are still useful for cost‐efficient mutation detection and for the interpretation of large‐scale genetic data made available by next generation sequencing strategies.